Biochemical response of the clam Ruditapes philippinarum to silver (AgD and AgNPs) exposure and application of an integrated biomarker response approach. (December 2019) - Aouini, Fatma; Trombini, Chiara; Sendra, Marta; Blasco, Julian
Abstract: Silver is a ubiquitous metal in the marine environment which can be accumulated by marine organisms. In order to assess the effect of dissolved silver (AgD) and AgNPs in R. philippinarum, the organisms were exposed to 20 μg L −1 of AgD and AgNPs (15 nm) over 7 days. Bioaccumulation of the metal and oxidative and detoxification biomarkers were studied in control and exposed clams. Ag was accumulated in gills and digestive glands. Results for biochemical biomarkers (superoxide dismutase, catalase and glutathione reductase activity, lipid peroxidation and metallothionein provoked a general increase in the integrated biomarker response index (IBR) values) indicating the induction of oxidative stress in the clams exposed to both Ag treatments. Therefore, the presence of Ag forms at the tested concentration in the aquatic medium represent a risk for R. philippinarum . Highlights: Exposure of Ruditapes philippinarum to dissolved silver and silver nanoparticles. Silver concentration was similar in the digestive gland, independently of the form of Ag. Silver accumulation was higher for AgD than AgNPs in the gills. Both Ag forms are able to induce oxidative stress in both tissues. IBR index showed a tissue specific response to each form of Ag.